Dynamics of minerals and nutrient imbalances in olive leaves under tillage and annual legume cover crops - Correia, Carlos M. (2019)
The concentration of minerals in leaves depends on phenology, crop yield, soil characteristics, environmental conditions and agronomic practices. This study was undertaken to compare the dynamics of minerals of olive rainfed trees under tillage (two per year) with trees in consociation with a mixture of 11 early season self-reseeding Legumes. The results of leaf minerals concentrations, on both treatments, showed similar variation between sampling dates, with higher levels of N, P, K, B and Zn found in summer, at endocarp sclerification, and of Ca, Mg, Fe and Mn at winter resting period, resulting in statistically significant changes on nutrient ratios, with higher Ca, Mg, Fe and Mn-to-N and Ca:Mg and Fe:Mn ratios and Lower K, P, B, Cu and Zn-to-N and K:Ca, K:Mg, Cu:Zn, Zn:Fe and Zn:Mn ratios during winter. Trees of plots managed with the cover crop had higher concentrations of N, Mg and Mn, in close association with leaf water status, photosynthetic activity and crop yield. Moreover, legumes plots presented significant higher Mg and Mn-to-N ratios and Lower P, Fe and 8-to-N ratios, as well lower K:Mg, Ca:Mg, Fe:Mn and Zn:Mn ratios on both dates, and lower K and Cu-to-N ratios during summer. Although only Cu values were higher than typical sufficient Levels, important relative nutrient changes were found. Phosphorus and Mg-to-N ratios were above the optimal ratios for olive leaves, on both seasons, the Fe: N ratio was over during winter, the Mn:N ratio was higher under cover crop, the K:N ratio was Lower at winter and Ca:N was below the reference Levels during summer. These results highlighted that nutrient ratios can be more indicative than nutrient concentrations regarded as optimal for olive. lt is important to standardise the procedures for leaf sampling and to define target values for nutrient ratios in different conditions, in order to detect and, if necessary, to correct nutrient imbalances.